(untitled) (Central Medical College Journal, 2025)
Background: Lateral epicondylitis (LE) commonly known as tennis elbow, is a degenerative condition affecting the myotendinous junction of the wrist extensors at the lateral epicondyle, predominantly causing pain and reduced function in the affected arm. It is commonly seen in individuals over 45 years old who engage in high-risk activities involving repetitive wrist extension. Conservative management is the mainstay of treatment, but dry needling (DN) is a newer technique with limited evidence in treating LE. Methods: This study involved patients diagnosed with lateral epicondylitis at a tertiary care hospital in Bangladesh. Participants were divided into two groups: one receiving dry needling combined with conservative management, and the other receiving conservative management alone. Pain and functional outcomes were measured using the Patient-Rated Tennis Elbow Evaluation (PRTEE) and the Visual Analog Scale (VAS) at baseline, 1 month, and 3 months post-treatment. Results: A total of 60 patients with lateral epicondylitis were enrolled and randomized into two groups: Group A (n=30) received dry needling in addition to conservative management (oral acetaminophen, exercises, and elbow counterforce brace), while Group B (n=30) received conservative management only. After accounting for losses to follow-up, 28 patients in Group A and 27 in Group B completed the 3-month follow-up. Baseline demographic and clinical characteristics were comparable between the groups (p>0.05). At 1 and 3 months, Group A showed significantly greater improvements in PRTEE pain, functional, and total scores compared to Group B (p<0.001). VAS scores also demonstrated significantly greater pain reduction in Group A at both follow-ups (p<0.001). Group A maintained progressive improvement over time, whereas Group B exhibited initial improvement at 1 month followed by regression toward baseline at 3 months. These findings suggest that dry needling, when combined with standard conservative treatment, offers superior and sustained clinical benefits in managing lateral epicondylitis. Conclusion: Dry needling, when combined with conservative management, appears to be an effective treatment for lateral epicondylitis, offering sustained improvements in pain and function. This technique could be a valuable adjunct to traditional treatments, although further studies with larger sample sizes are needed to confirm these findings. Central Medical College Journal Vol 9 No 1 January 2025 Page: 23-30